Xi Jinping, “China Dream”, and Chinese Military Diplomacy to ASEAN - Lidya Christin Sinaga (JAS (Journal of ASEAN Studies), 2020)
The rise of Xi Jinping has brought together the idea of the ‘China Dream’ as a great revival of China. Since the dream referred to the nationalism spirit of a ‘century of humiliation,’ it has made national security issues as the core of China’s diplomacy. While the national security-related foreign policy has enhanced the military's role in China’s foreign policy-making, it brings consequences for China’s tougher stance in protecting China’s national security. However, Xi Jinping’s notion of using military diplomacy has started uneasy relationships between China and some ASEAN countries resulting in ‘ongoing negotiation without progress’ for the South China Sea dispute. The research examines the impacts of the military’s growing role in China’s foreign policy under Xi Jinping to its military diplomacy in ASEAN. The results show that Xi Jinping’s leadership and vision of the China Dream, which uses military diplomacy as a key tool for advancing its whole diplomatic goals, has been seen as a sign of growing assertiveness.